Estimation of serum calcitonin, phosphate, and calcium in type 2 diabetes mellitus - Maaroof Taher, Zahraakhan; Nouri Ahmed, Sardar (Zanco Journal of Medical Sciences (ZJMS), 2023)
Background and objective: Type two diabetes is known as insulin-independent diabetes mellitus due to body’s inability to respond to insulin and can be managed by lifestyle change and hypoglycemic tablets. This study aimed to compare serum levels of calcitonin, calcium, and phosphate between type two diabetic patients and controls. Methods: The cross-sectional study included 50 patients who have already been diagnosed with type two diabetes mellitus and 50 control subjects without clinical signs of any diseases. The level of serum calcitonin, calcium, and phosphate was estimated for all participants. Results: The mean serum level of calcitonin was (2.35 ± 1.18) pg/mL in the case group, while the mean was (32.91 ± 3.88) pg/mL in the control group (P-value = 0.001). The mean level of serum phosphate was (3.93 ± 0.08) mg/dL and (3.73 ± 0.09) mg/dL in the case and control groups, respectively (P-value = 0.117). The mean serum calcium level was (9.68 ± 0.10) mg/dL in the case group, and it was about (9.67 ± 0.14) mg/dL (P-value = 0.955) in healthy persons. Serum calcitonin was negatively correlated with glycated hemoglobin and serum glucose level. Conclusion: The calcitonin serum level in diabetic patients was significantly lower than in healthy individuals. The level of bone minerals (calcium and phosphate) was not altered in type two diabetic patients when compared with control participants.